Extent to which the Competencies for the General Education Realized in BIBCHUR (European Journal of Teaching and Education, 2022)
This study uses a descriptive-evaluative approach in determining students’ perspectives in one of their courses, Bible and Church (BIBCHUR). The goal is to evaluate competencies/learning outcomes developed by the Commission on Higher Education (CHED) of the Philippines for the Revised General Education Curriculum (RGEC) vis-à-vis the new GE Institutional Requirement course Bible and the Church offered at De La Salle-College of Saint Benilde. Results of the qualitative study show that the five Intellectual General Education (GE) Competencies identified by CHED were realized in BIBCHUR only to a moderate extent. There is a need to enhance the language, information processing, and reasoning skills by giving students more reflective activities to highlight outcomes than knowledge. In conclusion, to make the course more relevant to the students, re-training of teachers in the implementation of OBE, learning management system (BigSky), and Inclusion, especially in the areas of delivery, assessment, and grading should be reconsidered.